Cristãos-novos, Jesuítas e Inquisição: uma relação controversa em Portugal (séculos XVI e XVII) - Franco, José Eduardo (2016)
Este artigo procura analisar aspectos das relações complexas entre os Jesuítas, Tribunal da Inquisição e Cristãos-Novos. A colaboração de jesuítas com as estruturas do Santo Ofício não obstou a que surgissem dentro da Companhia de Jesus vozes fortemente críticas e discordantes do modo de atuar daquele Tribunal que foi observado com prudência por parte das primeiras lideranças jesuítas. Por seu lado, os Cristãos-Novos tiveram desde o início grande acolhimento no seio da Ordem de Santo Inácio, destacando-se alguns descendentes de judeus à frente de posições de governo na Companhia de Jesus, a começar pelo segundo Superior Geral. Ao longo da história difícil de intolerância e perseguição inquisitorial em relação aos cristãos-novos estes encontraram destacados defensores da sua causa na Companhia de Jesus. Estas relações dilemáticas fazem desta relação triangular um tema historiográfico importante para compreender os tramas e dramas da sociedade o Antigo Regime.********************************************************************Christians-New, Jesuits and Inquisition: a relationship controversial in Portugal (sixteenth and seventeenth centuries)Abstract: This paper analyses aspects of the complex relationship between the Jesuits, the Inquisition Court and the New Christians. The collaboration of Jesuits with the Holy Office institutions did not prevent that within the Society of Jesus there were strong critical and discordant voices being raised against this Court’s practices, which were observed with caution by the first Jesuit leaders. For their part, the New Christians enjoyed a great reception within the Order of St. Ignatius from the beginning, with some Jewish descendants standing out in high positions in the Society of Jesus, such as the second Superior General. Throughout the difficult history of intolerance and inquisitorial persecution against the New Christians, the Jesuits were prominent advocates of their cause. These problematic relationships make this triangular relationship an essential historiographical subject in order to understand the plots and dramas of the Old Regime society.Keywords: Judaism; Inquisition; New Christians; Jesuits; Portugal; Old Regime.